The Association between Gly460Trp-Polymorphism of Alpha-Adducin 1 Gene (ADD1) and Arterial Hypertension Development in Ukrainian Population - Svitlana Yermolenko; Yaroslav Chumachenko; Viktor Orlovskyi; Irina Moiseyenko; Oleksandr Orlovskyi (International Journal of Hypertension)
Arterial hypertension (AH) belongs to the diseases with genetic predisposition that determines the necessity of research on the genetic component’s influence on this disease development. It is suggested that one of the salt-sensitive arterial hypertension potential markers may be the alpha-adducin gene because its protein product is involved in the ion transport regulation in the renal epithelium. Thus, the aim of the study was to investigate the association between ADD1 Gly460Trp-polymorphism and the AH development risk among patients with different risk factors in the Ukrainian population. The study included 232 Ukrainians: 120 patients with diagnosed arterial hypertension and 112 practically healthy individuals. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis was used for ADD1 Gly460Trp-polymorphism genotyping. The ADD1 Gly460Trp-polymorphic locus is an important predictor of arterial hypertension development in the Ukrainian population, but other nongenetic factors should be considered in further studies.